Beyond Standardized Leadership: An Adaptive-Contextual Model of School Principal Leadership in a Remote Highland School in Papua, Indonesia - Tori Wakerkwa; Jeffry S.J. Lengkong; Zoya F. Sumampow; Romi J. Mongdong (JR Education, 2026)
Effective school leadership remains decisive for educational quality, yet principals serving in Indonesia’s frontier, outermost, and disadvantaged (3T) regions, particularly in the highlands of Papua, must lead under extreme geographic isolation, severe resource scarcity, and culturally distinct community structures that single-style leadership theories rarely capture as an integrated whole. This study aimed to identify the leadership style applied by the principal of SMA Negeri 1 Pirime, Lanny Jaya Regency, Papua Highlands Province, and to explore the internal and external factors that support and hinder its implementation. A qualitative descriptive design was employed; data were collected through in-depth interviews with the principal, teachers, administrative staff, and a school committee representative, complemented by participatory observation and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Results show that the principal did not rely on a single leadership style but integrated four complementary approaches, transformational, participative/democratic, culturally responsive, and situational leadership, into one cohesive practice. Transformational leadership substituted for the absence of physical facilities by mobilizing teachers’ motivation and moral commitment; participative and culturally responsive approaches secured social legitimacy by embedding customary and religious values into school governance; and situational leadership enabled differentiated guidance according to teachers’ varying competence. Supporting factors were dominated by social capital, the principal’s personal integrity, teachers’ sense of vocational calling, and strong community-religious respect for educators, while inhibiting factors centered on geographic isolation, the absence of connectivity, uneven teacher competence, early-marriage practices, and uniform national policy standards poorly suited to remote contexts. The study concludes that this practice constitutes an emergent Adaptive-Contextual Leadership model in which social and cultural capital substitute for missing physical and technological resources to sustain meaningful education delivery under extreme constraints. These findings imply that principal preparation programs and education policy for Indonesia’s 3T regions should shift from uniform, facility-based standards toward context-sensitive frameworks that formally recognize local social and cultural capital as legitimate educational resources.